PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN STUNTING PADA IBU HAMIL DAN IBU BALITA DI DESA KESESIREJO BODEH PEMALANG - Qomariyah, Qomariyah; Rizqi Wulandari; Alisa Qotrunnnada (Bajang Institute, 2025)
Maintaining nutritional balance in pregnant women is very necessary so that the condition of the mother and fetus remains healthy by providing sufficient food containing carbohydrates and fats as a source of energy. And as a source of protein building materials, get additional iron, calcium, vitamins, folic acid and energy. The purpose of this activity is to increase the knowledge of pregnant women about balanced nutrition in preventing stunting. The general purpose of this activity is After the counseling is complete, participants can learn about balanced nutrition for pregnant women in early prevention of stunting. The benefits of this activity are expected that pregnant women can increase their knowledge in balanced nutrition to prevent stunting in Kesesirejo Village, Bodeh District, Pemalang Regency.